TOEFL grammar flash = The quick way to build grammar power - Broukal, Milada; Nguyễn Văn Phước; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2003)
Types of structure and written expression questions; Structure and written expression practice tests.
Keywords: Anh ngữ; English language; TOEFL; Anh ngữ -- Luyện thi; English language -- Tests